(untitled) (Impact: Journal of Transformation, 2023)
This study examines the teaching of the prosperity gospel to see whether its overall emphasis aligns with the wider ideals of transformational development, as particularly popularised by Bryant Myers. Proponents of the prosperity gospel claim that financial riches and success are markers of God’s favour and that when individuals align their thoughts and actions with God’s will, they may unleash a life of prosperity. On the other hand, transformational development is a holistic strategy for addressing material poverty as well as social, political, and spiritual challenges. It also strives to empower people, communities, and society to alter their lives and achieve long-term change. The research question that underlies this study is: Does the prosperity gospel fulfill the purpose of transformational development? The research is a theological assessment of the teachings of the prosperity gospel, partly seeking to identify its positive aspects. Teachings by selected preachers of the prosperity gospel, such as Enoch Sitima of Botswana, Mensa Otabil of Ghana, and David Oyedepo of Nigeria, are accessed through the internet, books written by or ascribed to them, and claims that are attributed to them. These teachings were assessed in the context of transformational development, including the interpretation of pertinent biblical texts that serve as the foundation for prosperity preaching. From the interaction with the teaching of the prosperity gospel, it is evident that while the teaching caters to the fundamental areas of human life, it leaves believers with the tendency to maintain a utilitarian relationship with God.